Evolution of an Approach to the Problem of Relations which Public Authority May Enter, as a Condition for EU Membership - Potorski, Radosław (The Copernicus Journal of Political Studies, 2018)
In the light of the evolution of political systems the classical model of national state does not have the potential to fully explain the complex of a state (public power) both current state and international relations. The new forms of governing the international markets and other economic processes, currently emerging, are engaging national governments. However, given a new role, the countries begin to function less as “sovereign” beings and more as components of international political community. At the same time occurs the engagement of non-governmental actors, employed to make important public decisions – it redefines society from being an object of governance to being a potential resource that needs to be activated in the pursuit of good public governance. That is why, moving away from the centrally understood model of decision-making known from the nation-state determines understanding of modern relations that public authority takes part in (such as the membership in the structures of the European Union – which is connected to a change in conditions of established patterns of governing). To explain that phenomenon it is used the concept of a hollow state. Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14761